My Life And Work (The Autobiography Of Henry Ford) - Henry Ford (Germany BN Publishing, 2008)
"My Life and Work" is the autobiography of Henry Ford. Written in conjunction with Samuel Crowther, "My Life and Work" chronicles the rise and success of one of the greatest American entrepreneurs and businessmen. Henry Ford and the Ford Motor Company will forever be identified with early 20th century American industrialism. The innovations to business and direct impact on the American economy of Henry Ford and his company are immeasurable. His story is brilliantly chronicled in this classic American biography.
Keywords: Biography; Autobiography; Business; History; Nonfiction; Memoir